The home disadvantage in championship competitions: team sports - Jones, M. B. (Psychology of Sport and Exercise, 2014)
Objectives: The possibility that home teams might choke in decisive games of championship series was first proposed by Baumeister and Steinhilber in 1984. Their hypothesis was that when the home team was on the verge of winning a championship, it tended to choke. As a result, the home advantage would be smaller in last games than in early games of the same series. The present paper updates the original data for baseball and basketball to 2012 and adds a parallel study of ice hockey. Design/Method: The analysis compares home win percentage early in a championship series with home advantage in the regular season. Its main focus, however, is on the games in a championship series between the early and late games. Results: The first of two main results is that in all three sports the percentage of home wins in Game 1 of a championship series is substantially higher than home advantage in the same sport in the regular season. The second result is that, while the tendency for percent home wins to decrease regularly over the course of a best-of-seven series is confirmed in all three sports, this decrease is complete or almost complete by Game 4, well before the home choke, according to Baumeister and Steinhilber, is supposed to occur. Conclusion: The home-choke hypothesis as originally advanced in 1984 is not supported by subsequent results and analysis.